2023
DOI: 10.1186/s40462-023-00379-0
|View full text |Cite
|
Sign up to set email alerts
|

Diverse environmental cues drive the size of reproductive aggregation in a rheophilic fish

Abstract: Background Animal migrations are periodic and relatively predictable events, and their precise timing is essential to the reproductive success. Despite large scientific effort in monitoring animal reproductive phenology, identification of complex environmental cues that determine the timing of reproductive migrations and temporal changes in the size of reproductive aggregations in relation to environmental variables is relatively rare in the current scientific literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…They also observed a high frequency of skipped spawning, which likely serves as an adaptive behaviour to mitigate impacts of environmental variability. Šmejkal et al [ 23 ] monitor reproductive aggregations of asp ( Leuciscus aspius ) in a Želivka Reservoir tributary in the Czech Republic in relation to different environmental cues, including water temperature, discharge, temperature, precipitation, atmospheric pressure, wind speed and lunar phase, as well as temporal changes. The study shows that the observed variability is sex-dependent, with reproductive aggregation size being positively affected by water temperature and wind speed, and highest during the period before and after the full moon and at night.…”
Section: About the Thematic Seriesmentioning
confidence: 99%
“…They also observed a high frequency of skipped spawning, which likely serves as an adaptive behaviour to mitigate impacts of environmental variability. Šmejkal et al [ 23 ] monitor reproductive aggregations of asp ( Leuciscus aspius ) in a Želivka Reservoir tributary in the Czech Republic in relation to different environmental cues, including water temperature, discharge, temperature, precipitation, atmospheric pressure, wind speed and lunar phase, as well as temporal changes. The study shows that the observed variability is sex-dependent, with reproductive aggregation size being positively affected by water temperature and wind speed, and highest during the period before and after the full moon and at night.…”
Section: About the Thematic Seriesmentioning
confidence: 99%